Effects of Intradialytic Cognitive and Physical Exercise Training on Cognitive and Physical Abilities in Hemodialysis Patients: Study Protocol for a Randomized Controlled Trial - Bogataj, Špela; Trajković, Nebojša; Pajek, Maja; Pajek, Jernej (Frontiers in Psychology, 2022)
The prevalence of cognitive impairment in hemodialysis (HD) patients is extremely high. Despite the well-documented benefits of interventions on cognitive function, there is a widespread call for effective strategies that will show the long-term consequences in patients undergoing dialysis. The aim of this research protocol was to investigate the effect of cognitive training combined with physical exercise on cognitive function, physical performance, and frailty indicators in the HD population. We will conduct a randomized controlled intervention trial to examine the effects of a combined non-pharmacological intervention in the form of intradialytic physical exercise and intradialytic cognitive training on cognitive function, indicators of frailty, and physical performance measures in HD patients. The group of patients receiving the study intervention will be compared to the control group receiving standard HD care. The duration of the intervention will be 12 weeks. We will use sensitive instruments (cognitive domain tests) to assess cognitive functions. The primary outcome of the study at 12 weeks will be performance on the Alertness subtest of the computerized Test of Attentional Performance. Secondary study outcomes are: Performance in other domains of cognitive function (executive function, psychomotor speed, information processing efficiency, working memory, and attention), physical fitness (10 repetition sit-to-stand test, timed up and go test, handgrip strength test, spontaneous gait speed, and stork balance test), and assessment of frailty (Edmonton Frail Scale). Study outcomes will be assessed at baseline, immediately after the 12-week intervention, and 6 months after the end of the study without specific further intervention (retention effect assessment). This study will be among the first to test the synergistic effects of a uniquely designed physical exercise and cognitive training intervention on functional status in HD patients. We believe our results will contribute to dementia prevention research by demonstrating the long-term efficacy of our combined intervention. Clinical Trial Registration:ClinicalTrials.Gov, NCT05150444.